HUBUNGAN ANTARA DAYA LEDAK TUNGKAI DAN KESEIMBANGAN DENGAN KEMAMPUAN LARI 50 METER PADA MURID SD NEGERI 1 KOTABARU HULU - M. Imran Hasanuddin (STKIP Paris Barantai, 2015)
This study is the kind of research the descriptive. This study aims to know: (1) whether there is the contribution between explosive power leg with the ability run 50 meters students SD Negeri 1 Kotabaru Hulu. (2) whether there is the contribution between balance with the ability run 50 meters students SD Negeri 1 Kotabaru Hulu. (3) whether there is the contribution between explosive power leg and balance with the ability run 50 meters students SD Negeri 1 Kotabaru Hulu. The population is students SD Negeri 1 Kotabaru Hulu. Samples used is the male students SD Negeri 1 Kotabaru Hulu as much forty people. The techniques determination of these samples are with the ramdomly with the way the lottery (Simple Random Sampling).Â Analysis technique used data is analysis the descriptive and analysis infernsial through the SPSS 20 on degree significantÎ±0,05. The results of research suggests that: (1) There is the contribution between explosive power legÂ with the ability run 50 meters students SD Negeri 1 Kotabaru Hulu, by 63,3%. (2) There is the contribution between balance with the ability run 50 meters students SD Negeri 1 Kotabaru Hulu, by 17,5%. (3) There are contributions significant in together between explosive power leg and balance with the ability run 50 meters students SD Negeri 1 Kotabaru Hulu, with the value of F:32,794 and sig (p)=0,000.Â Key words : explosive power leg, balance, run 50 meters.